Factors Influence Non-suicidal Self-Injury Behavior among Young Adults - Herdaetha, Adriesti; Ismaya, Matius Dimas Reza Dana; Suwito, Joko (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Non-suicidal self-injury (NSSI) behavior is increasing among young adults in Indonesia due to the experienced stress. This behavior is influenced by sleep quality, parenting style, and alexithymia mediated by emotional dysregulation. Objectives: To determine the influence of sleep quality, parenting style, and alexithymia on NSSI behavior mediated by emotional dysregulation in the young adult population. Methods: This study used an analytical observational design with a cross-sectional approach. The study subjects consisted of 573 young adult respondents who met the inclusion and exclusion criteria. The study was conducted using a Google Form distributed through social media. Statistical tests were performed using structural equation modeling-partial least square (SEM-PLS). Results: Directly, sleep quality increased NSSI (p=0,000; OS=0,219) and emotional dysregulation (p=0,012; OS=0,076), authoritative parenting style decreased emotional dysregulation (p=0,000; OS=-0,109), authoritarian parenting style increased NSSI (p=0,013; OS=0,125), alexithymia increased emotional dysregulation (p=0,000; OS=0,655), and emotional dysregulation increased NSSI (p=0.000; OS=0.252). Indirectly, through emotional dysregulation mediation, sleep quality increased NSSI (p=0,032; OS=0,019), authoritative parenting style decreased NSSI (p=0,008; β=-0,027), and alexithymia increased NSSI (p=0,000; OS=0,165). Conclusions: Sleep quality, parenting style, and alexithymia influence NSSI behavior directly and indirectly through emotional dysregulation mediation.